Hyperosmolar Stress Induces Neutrophil Extracellular Trap Formation: Implications for Dry Eye Disease - Tibrewal, Sapna (Invest Ophthalmol Vis Sci, 2014)
PURPOSE. To determine if hyperosmolar stress can stimulate human neutrophils to form neutrophil extracellular traps (NETs) and to investigate potential strategies to reduce formation of NETs (NETosis) in a hyperosmolar environment. METHODS. Neutrophils were isolated from peripheral venous blood of healthy subjects and incubated in iso-osmolar (280 mOsM) or hyperosmolar (420 mOsM) media for 4 hours. Neutrophil extracellular traps were quantified using a PicoGreen dye assay to measure extracellular DNA. Two known inhibitors of NETosis, staurosporine and anti-β2 integrin blocking antibody, and two proresolution formyl peptide receptor 2 (FPR2) agonists, annexin/lipocortin-1 mimetic peptide and 15-epi-lipoxin A(4), were evaluated as possible strategies to reduce hyperosmolarity-induced NETosis. RESULTS. The amount of NETs induced by hyperosmolar medium (420 mOsM) increased linearly over time to 3.2 ± 0.3 times that induced by iso-osmolar medium at 4 hours (P < 0.05). NETosis increased exponentially with increasing osmolarity and was independent of the stimulus used to increase osmolarity. Upon neutrophil exposure to hyperosmolar stress, restoration of iso-osmolar conditions decreased NET formation by 52.7% ± 5% (P < 0.05) but did not completely abrogate it. Among the strategies tested to reduce NETosis in a hyperosmolar environment, annexin-1 peptide was the most efficacious. CONCLUSIONS. Hyperosmolarity induces formation of NETs by neutrophils. This NETosis mechanism may explain the presence of excessive NETs on the ocular surface of patients with dry eye disease. Because they reduce hyperosmolarity-induced NETosis, FPR2 agonists may have therapeutic potential in these patients.